2021
DOI: 10.1155/2021/6811192
|View full text |Cite
|
Sign up to set email alerts
|

Signal Recognition for English Speech Translation Based on Improved Wavelet Denoising Method

Abstract: The signal corresponding to English speech contains a lot of redundant information and environmental interference information, which will produce a lot of distortion in the process of English speech translation signal recognition. Based on this, a large number of studies focus on encoding and processing English speech, so as to achieve high-precision speech recognition. The traditional wavelet denoising algorithm plays an obvious role in the recognition of English speech translation signals, which mainly depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…After the original speech signal is pre-processed by noise reduction and other pre-processing, the first step is to extract features from speech data. From the existing research literature, it can be found that at this stage, acoustic feature extraction mainly adopts the Hidden Markov Chain for pattern recognition of the collected digital speech sequences, i.e., to realize the primitive classification of digital speech sequences [25][26].…”
Section: English Speech Recognition Processmentioning
confidence: 99%
“…After the original speech signal is pre-processed by noise reduction and other pre-processing, the first step is to extract features from speech data. From the existing research literature, it can be found that at this stage, acoustic feature extraction mainly adopts the Hidden Markov Chain for pattern recognition of the collected digital speech sequences, i.e., to realize the primitive classification of digital speech sequences [25][26].…”
Section: English Speech Recognition Processmentioning
confidence: 99%
“…Zhao, X. et al combined artificial intelligence with English machine translation, which innovated the English translation teaching mode, and promoted the development of the language education industry [15]. Chen, Z. used the improved wavelet denoising algorithm to recognize the English speech translation signals as a way of realizing high-precision English translation speech recognition, and solved the distortion situation in the recognition process of English speech translation signal, enhanced the recognition ability of English speech, and provided effective English speech for college students to learn English translation [16]. Karasaliu, A. analyzed the problems and difficulties in the process of English translation teaching and verified based on the data of students' questionnaires that teachers attitudes in carrying out English translation Teachers' attitudes in conducting English translation will affect students' ability to learn English translation, and there will be a certain gap in students' attitudes towards English translation teaching [17].…”
Section: Introductionmentioning
confidence: 99%
“…Guo proposed a fuzzy algorithm to improve the performance of the English translation system by using the DNN-HMM speech recognition model and the traditional GMM-HMM speech recognition model to corpus and apply a small amount of training data to synthesize the information [15]. Chen used an improved wavelet denoising method for language recognition and used coding processing for English speakers, which effectively improved the recognition rate of speech and the accuracy of translation [16]. Ban and Ning studied Chinese-English machine translation based on deep neural networks, and the study showed that deep neural networks effectively improved the performance of translation and the system had higher usability [17].…”
Section: Introductionmentioning
confidence: 99%